Phylogenetic relationships of dasyuromorphian marsupials revisited. (10th November 2015) - Westerman, Michael; Krajewski, Carey; Kear, Benjamin P.; Meehan, Lucy; Meredith, Robert W.; Emerling, Christopher A.; Springer, Mark S.
Abstract : We reassessed the phylogenetic relationships of dasyuromorphians using a large molecular database comprising previously published and new sequences for both nuclear (nDNA) and mitochondrial (mtDNA) genes from the numbat ( M yrmecobius fasciatus ), most living species of Dasyuridae, and the recently extinct marsupial wolf, T hylacinus cynocephalus . Our molecular tree suggests that Thylacinidae is sister to Myrmecobiidae + Dasyuridae. We show robust support for the dasyurid intrafamilial classification proposed by Krajewski & Westerman as well as for placement of most dasyurid genera, which suggests substantial homoplasy amongst craniodental characters presently used to generate morphology‐based taxonomies. Molecular dating with relaxed molecular clocks suggests that dasyuromorphian cladogenesis began in the Eocene, and that all three dasyuromorphian families originated prior to the end of this epoch. Radiation within Thylacinidae and Dasyuridae had occurred by the middle to late Oligocene, consistent with recognition of primitive thylacinids (e.g. B adjcinus turnbulli ) in the later Oligocene and of putative dasyurids (e.g. B arinya wangala ) by the early Miocene. We propose that all four extant dasyurid tribes were in existence by the early Miocene and that most modern dasyurid genera/species were established before the later Miocene. This is in marked contrast to the popularly accepted advocation of their origins in the latest Miocene–early Pliocene. © 2015 The Linnean Society of London